Material culture : aspects of contemporary Australian craft and design - Bell, Robert, 1946-; National Gallery of Australia (Canberra : National Gallery of Australia, 2002)
Outlining aspects of contemporary Australian craft and design, this book focuses on recent works in ceramics, glass, textiles, furniture, jewellery and metal.
Foreword / Brian Kennedy -- Introduction / Robert Bell -- Structure -- Robert Baines -- Frank Bauer -- Matthew Curtis -- Mark Edgoose -- Viliama Grakalic -- Johannes Kuhnen -- Sue Lorraine -- Klaus Moje -- Catherine Truman -- Jenny Turner -- Richard Whiteley -- Narrative -- Janet DeBoos -- Anne Dybka -- Tony Hanning -- Brian Hirst -- Kay Lawrence -- Jessica Loughlin -- Helmut Lueckenhausen -- Jeff Mincham -- Milton Moon -- Nick Mount -- Kevin Perkins -- Denise Sprynskyj and Peter Boyd -- Transformation -- Les Blakebrough -- Pippin Drysdale -- Marian Hosking -- Helge Larsen and Darani Lewers -- Mitsuo Shoji -- Alan Watt -- Margaret West -- Maureen Williams -- Liz Williamson.
Includes bibliographical references (p. 80).
Keywords: National Gallery of Australia -- Exhibitions; Decorative arts -- Australia -- History -- 20th century -- Exhibitions; Decorative arts -- Australian Capital Territory -- Canberra -- Exhibitions